A Marxist Reading of Snow-Bound: Interpellation through examination of domestic ideology, imagery and symbolism - Zaid Tayyeh Bakhsh (Peerian Journals Publishing, 2024)
Most of the work that Marxist pundits have done, has been on volumes scholarly works, since they accept that bigger scholarly works give more space for the portrayal of diverse layers of society, hence books have been among favorite targets of Marxist feedback, but when it comes to the subject of “interpellation” which we are to join here, realistic novels are the most excellent targets for an Althusserian feedback since they can be most intelligent of societies' structures .In spite of the fact that not a long work and not a novel however Snow-Bound: An Idyll Winter, may be a sonnet based on genuine characters and mostly on genuine individual encounters that were nostalgic for the perusers at that time. Hence this lyric can be intelligent of its contemporary social structure. But what here is getting to be beneath our examination is the impacts that Snow-Bound takes off on the perusers. Snow-Bound was a success which demonstrates the product nature of Snow-Bound as created inside the cogs of capitalistic machine. What this lyric produces semantically, how it is produces basically, and how this sonnet impacts the perusers is the essence of this paper . We have accepted that this lyric interpellates the perusers, that's it gives the perusers the daydream of having an autonomous character, an character not influenced by social structures. To demonstrate this, we have analyzed the symbolism and imagery working inside the lyric, on the other hand we have inspected the residential belief system of the lyric and the sexual orientation parts that work inside the sonnet.
Keywords: Imagery; Symbolism; Domestic Ideology; Interpellation